2013
DOI: 10.1159/000355928
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of GHR Should Contain Sequencing of All Coding Exons and Specific Intron Sequences, and Screening for Exon Deletions

Abstract: Background: The work-up of patients with clinical and/or biochemical features of growth hormone insensitivity (GHI) usually contains genetic analysis of the growth hormone receptor (GHR) gene, and if negative, of STAT5B, IGFALS and IGF1. In a previous report we described 2 siblings presenting with short stature, low IGF-1 levels, elevated GH secretion and no increase of IGF-1 after 1 week of GH administration. Repeated analysis of the GHR showed no abnormalities; however, further testing revealed a heterozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Unfortunately, we were unable to perform segregation studies as parental DNA was not available for any of the subjects. However, consistent with our findings, a previous study of two 6Ψ patients also demonstrated that other genetic variants did not contribute to the severity of the phenotypes (20).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Unfortunately, we were unable to perform segregation studies as parental DNA was not available for any of the subjects. However, consistent with our findings, a previous study of two 6Ψ patients also demonstrated that other genetic variants did not contribute to the severity of the phenotypes (20).…”
Section: Discussionsupporting
confidence: 93%
“…Genotyping a region spanning 17.10 Mb around the GHR gene on chromosome 5 and analysis of the complex single polymorphic region in intron 9 of the GHR in five GHR 6Ψ families showed the same genotype for all affected members, suggesting the presence of a common ancestor (19). Furthermore, 19/22 of the known GHR pseudoexon patients are of Pakistani ethnicity (18,19,20,21). This implies that the GHR 6Ψ patient cohort share a common genetic background.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…material, see www.karger.com/doi/10.1159/000480505). Furthermore, we sequenced a GHR pseudo-exon intronic mutation (c.618+792A>G) by routine Sanger sequencing, which in affected individuals leads to an in-frame insertion of 36 amino acid residues [8]. …”
Section: Introductionmentioning
confidence: 99%